Photonic integrated circuits for NG-EPON - Rodrigues, Carla Iolanda Costa (2016)
Along with privacy and security, the growth of demand from the consumer for higher bandwidth presents one of the most important modern challenges in telecommunications infrastructures. The researchers were encouraged to nd not only e cient but also the economically viable solutions capable of meeting the growing needs of the consumer. Optical communications are the way that can accompany this growth. The Passive Optical Network (PON) is an architecture that shares the ber bandwidth among several users. There has been a constant study under this topic for the purpose of using all the ber abilities and to nd new solutions to keep the access network simple. Photonic Integrated Circuits (PICs) are a technology that emerged to help the complexity of the hardware that exists nowadays. It is a single chip capable of integrating numerous optical components, which leads to a reduced complexity, size and power consumption. These are the important characteristics that make the PICs a powerful tool to use in several applications. This dissertation presents a monolithic PIC transceiver in the context of Next Generation of Ethernet Passive Optical Network (NG-EPON) which aims to design and implement integrated optical circuits for future access networks. The transceiver architecture is able to be used as an Optical Network Unit (ONU) with a 4 channels approach for 100 Gb/s solutions. The present work contributed for the FUTPON project supported by P2020.